Gestión del agua para riego en prácticas de agricultura desde la complejidad ambiental (2018)
The environmental complexity gives to study the richness of species that occurs in different ecological systems, according to the impact generated by agriculture. Complexity analyzes all the parts of a system, interlacing each pattern with the other, in the environmental system the same anthropic activity in two similar ecosystems but in two different geographical places can cause a different impact from each other, this due to different cultures of each region. That is why to achieve the management of water resources in agro-industry it is necessary to understand and analyze the environmental networks. The environmental complexity gives rise to a vision of the individual as a subsystem and likewise to a system since what one individual directly or indirectly affects another as well as an ecosystem. There is no linearity in systems theory, which leads to analyze in environmental complexity several lines, orders, disorders, reversibility and irreversibility, predictable and unpredictable, agriculture and water management.